2002
DOI: 10.1016/s0030-4018(02)02120-x
|View full text |Cite
|
Sign up to set email alerts
|

Two-level laser light statistics

Abstract: The statistics of the light emitted by two-level lasers is evaluated on the basis of generalized rate equations. According to that approach, all fluctuations are interpreted as being caused by the jumps that occur in active and detecting atoms. The intra-cavity Fano factor and the photo-current spectral density are obtained analytically for Poissonian and quiet pumps. The algebra is simple and the formulas hold for small as well as large pumping rates. Lasers exhibit excess noise at low pumping levels.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2003
2003

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Consider now the very special case where γ = 0 and N ӷ α, i.e., the laser is thresholdless and has very low loss. The normalized photocurrent spectral density reads (12) Ᏽ is thus unity at low and high pumping levels and goes to a minimum in between these bounds. The minimum value, Ᏽ min , and the corresponding pumping value are (13) It can be shown that this minimum is the absolute minimum of Ᏽ, irrespectively of the values of γ, N, and α [7].…”
Section: (2)mentioning
confidence: 99%
See 1 more Smart Citation
“…Consider now the very special case where γ = 0 and N ӷ α, i.e., the laser is thresholdless and has very low loss. The normalized photocurrent spectral density reads (12) Ᏽ is thus unity at low and high pumping levels and goes to a minimum in between these bounds. The minimum value, Ᏽ min , and the corresponding pumping value are (13) It can be shown that this minimum is the absolute minimum of Ᏽ, irrespectively of the values of γ, N, and α [7].…”
Section: (2)mentioning
confidence: 99%
“…The numerical method and the analytical method are found to agree for the range of parameters considered. More extensive treatments considering other laser schemes will appear elsewhere [7,12]. Section 3 describes the complete treatment of a two-mode laser derived from a classical four-level scheme.…”
Section: Introductionmentioning
confidence: 99%